Brief dynamic interpersonal therapy a clinician's guide - Lemma, Alessandra; Target, Mary.; Fonagy, Peter, 1952- (Oxford : Oxford University Press, 2011)
This volume is a user-friendly, practical guide for the implementation of a brief psychodynamic intervention in routine clinical practice as well as in research protocols. It sets out clearly the theoretical framework, as well as the rationale and strategies for applying DIT with patients presenting with mood disorders.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Brief psychotherapy